Incorporating a risk assessment procedure into submarine outfall projects and application to portuguese case studies - Mendonça, A. C. (2013)
The paper presents a risk assessment methodology for operational limit states of submarine outfall projects that considers: the environmental legislative framework, the climate agents acting on the coastline and prediction of the plume long-term behaviour near the coastline. The probability of operational failure or stoppage is assessed enabling decision on project design alternatives.